Kebermaknaan Hidup pada Ibu yang Memiliki Anak Berkebutuhan Khusus - Muhimmatul Hasanah (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2023)
Mothers who have children with special needs regarding the meaning of life sometimes struggle to find meaning and purpose in life, leading a mother to approach life with passion, zest for life, far from feeling empty and patient in living life, and the strength to live everyday life to give meaning in his life in the goals to be achieved so that each activity becomes more focused. The purpose of this study is to describe the meaningfulness of life for mothers who have children with special needs. This study used qualitative research methods. This research uses a case study research type. The research subjects in this study were 3 parents who have children with special needs. This study uses a semi-structured in-depth interview method. In this study, the steps taken by researchers were qualitative data analysis according to Miles and Huberman's interactive model, namely data reduction, data modeling, drawing conclusions. In this study the data validity test was carried out by conducting technical triangulation. The results show that the three subjects have significance in everyday life. An overview of meaningfulness in life can be seen from the ability to understand life goals, freedom of desire, attitude towards death, and life satisfaction possessed by mothers who have children with special needs, in this case are mothers who have children with autism, mentally retarded and physically disabled